3D printed sandwich materials filled with hydrogels for extremely low heat release rate. (September 2020) - Geoffroy, Laura; Davesne, Anne-lise; Bellayer, Séverine; Blanchard, Florent; Richard, Elodie; Samyn, Fabienne; Jimenez, Maude; Bourbigot, Serge
Abstract: Additive manufacturing is a powerful tool to design materials with original properties. An innovative design of poly (Ethylene Vinyl Acetate) (EVA) containing 30 wt.-% of Aluminum TriHydroxide (ATH) was reported in a previous paper and liquids (water or potassium carbonate aqueous solution) were incorporated in the 3D printed structure. These multi-materials showing interesting properties, but stability, control and processing of these liquid-containing systems were an issue due to porosity of the polymeric matrix. To overcome this issue, the use of hydrogels is considered in this study: being either solid or highly viscous, hydrogels can retain water in the design, despite the high porosity of the EVA/ATH matrix. In this paper, the liquid phase was substituted by flame retardant hydrogels (based on agar, alginate or poly (vinyl alcohol) - PVA), containing in particular vermiculite platelets and for the hydrogel based on alginate, K2 CO3 as flame retardant fillers. Excellent behavior under a 50 kW/m 2 heat flux during a cone calorimeter test was obtained, with fast extinguishment of the flame and a low peak of Heat Release Rate (pHRR) and Total Heat Release (THR). The physical barrier formed by vermiculite platelets during the test, as well as the condensed phase mechanism of K2 CO3 were found to be responsible for these excellent results, as found by confocal microscopy observations, electron probe micro analysis and X-Ray diffraction experiments. Graphical abstract: Image 1 Highlights: New concept of flame retardant sandwich 3D printed materials. Creation of biphasic material containing hydrogel. Action in gas (K2 CO3 ) and condensed (clay and K2 CO3 ) phases.